Students' Understanding on Formal Definition of Limit. Issue 1 (February 2021) - Nurdin; Assagaf, S F; Arwadi, F
Abstract: This paper reports our preliminary findings of students' understanding on the formal definition of limit - epsilon delta definition. The aim of this study is to develop students understanding of definition of limit by construction learning trajectories in teaching limit. The subjects were five students majoring in mathematics. The methods were test and interview. The test is used to identify how the subjects proof the limit using formal definition. Interview aims to confirm and explore information about the students' difficulties in proving the limit using the definition. The interviews were then transcribed and analyzed along with the test results to get conclusions about the difficulties of students proving the limit by using formal definition. The result shows that the subjects were still facing difficulties in interpreting the definition of limits.